THE ROLE OF THE INTERSUBJECTIVE SOCIAL PARTNERSHIP IN THE REPUBLIC OF KAZAKHSTAN - A.Sansyzbayev,; Zh. Kenzhalina,; Zh. Malgaraeva, (Academic Journal of Physical and Chemical Sciences, 2019)
Nowadays, approaches in the theory of social partnership and social responsibility of business are developing intensively. This is due to the ongoing processes in the country. Today, the second stage of social modernization is being implemented. Therefore, this article timely examines approaches to the problem of intersubject social partnership. Since at present social management still poorly takes into account the resources of local communities, and above all the human, social and cultural potential, for the disclosure of these potentials, the priority is to transform the local community from an object of social policy into its subject. This implies the involvement of its active members in the formation of partner interaction systems and thereby reinforces the intersubjective significance of social partnership, which is still interpreted primarily as intersectoral. Thus, in modern conditions, the sociological analysis of social partnership should be directed not to the study of the sectors, but to the subjects of this interaction. The purpose of the articleis to conduct a theoretical analysis of approaches to the formation of intersubjective social partnership, which allows to improve the foundations of local governance.